Penentu Komunikasi Kepimpinan Dan Empowermen Terhadap Motivasi Kakitangan Awam Di Kuala Terengganu - Wan Mohd Amin, Wan Abd Aziz; Muda, Mohd Shaladin; Omar, Nik Wan; Abdullah, Wan Salihin Wong (Journal of Techno-Social, 2009)
The purpose of this study is to predict the determination of head’s leadership communication and empowerment staff on work motivation among public sector workers. Three construct leadership communications have been made into determining factor which is hacked out structure, communication consideration and orientation communication and the study will cover relationship between empowerment and work motivation. Sample only involve from state agency. They comprise of state agency and statutory body staff state. A sum of 108 samples employee from state agency department have been select by using random sampling technique and have been analyses with descriptive method, pearson colerasion, factor analysis and study shows the communication forecaster model that have been built are suitable with the collected study data. Furthermore leadership communication aspect and empowerment should have been given an emphasizing is one organization management to increase motivation among staff.